Pengujian Karakteristik Campuran HRS-WC menggunakan batu sungai Makawa Kecamatan Walenrang Utara - Kristiloresta Marianto; Alpius; Charles Kamba (Paulus Civil Engineering Journal, 2020)
This study was intended to examine the characteristics of the HRS-WC mixture by utilizing the Makawa river stone aggregate in North Walenrang District based on laboratory testing. The methodology in this research is to conduct a series of characteristics testing in the form of coarse aggregate, fine aggregate, filler and asphalt and then design the composition of the mixture then make the specimen in the form of HRS-WC mixture and conventional Marshall test for the determination of KAO after that making KAO test specimens to obtain the Immersion Index ( IP) / Residual Strength Index (IKS). The results of research conducted at the Road and Asphalt Laboratory of the Faculty of Civil Engineering, Indonesian Christian University Paulus Makassar, showed that the characteristics of the pavement material in the form of Makawa river stone aggregate in North Walenrang sub-district met the specifications of the road surface layer material. Through the Marshall test the HRS-WC mix characteristics were obtained with asphalt content of 5.9%, 6.4%, 6.9%, 7.4%, 7.9% fulfilling the requirements issued by the Directorate General of Highways of the Ministry of Public Works of the Republic of Indonesia , General Specifications2018. Marshall Immersion test results of HRS-WC mixture at optimum asphalt content of 6.4% get a Soaking Index (IP) / Residual Strength Index (IKS) / Durability of a mixture of 94.41% which means it exceeds the boundary conditions of ≥ 90% so the mixture is resistant to soaking in water.